2021
DOI: 10.1101/2021.03.18.21253604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rapid assessment of wastewater for genomic surveillance of SARS-CoV-2 variants at sewershed scale in Louisville, KY

Abstract: The successful viral detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in wastewater at various pooled scales (1-4) and discovery in the USA of B.1.1.7 , B.1.351 and P.1 variants (5), has led to an interest in developing reliable population-level wastewater viral genomic surveillance. The diversity of SARS-CoV-2 sequences reported to be circulating in the USA, have been determined by sequencing clinical samples; however, these variants can also be surveilled by sequencing wastewat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…To determine if our direct capture purification method yielded nucleic acid compatible with next-generation sequencing, we prepared sequencing libraries with a subset of wastewater samples using a commercially available SARS-CoV-2 amplicon panel and associated library preparation kit 46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…To determine if our direct capture purification method yielded nucleic acid compatible with next-generation sequencing, we prepared sequencing libraries with a subset of wastewater samples using a commercially available SARS-CoV-2 amplicon panel and associated library preparation kit 46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…Current mainstream methods for variant tracking in wastewater rely on enriching and sequencing of the environmental SARS-CoV-2 genome (Napit et al, 2021, Crits-Christoph et al, 2021Fontenele et al, 2021). This method, constrained by the same bottlenecks of cost and infrastructure requirement as clinical sequencing, is further hampered by challenges in detection of low-frequency variants and is poorly quantitative due to the lack of robust modelling to quantify variant titers (Fuqua et al, 2021;Van Poelvoorde et al, 2021) . RT-qPCR-based methods have been developed for variant identification in clinical samples (Clark et al, 2021;Vogels et al, 2021;Wang et al, 2021) Yaniv et al, 2021aYaniv et al, , 2021bWurtzer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have begun to identify known genotypes of SARS-CoV-2, as well as the variants recovered from sewers, but these studies remain scarce [ 38 , 39 , 40 , 41 , 42 , 43 ]. In this context, genotyping by sequencing SARS-CoV-2 from wastewater in the city of Marseille was undertaken using different methods, and the results correlated with the results of sequencing in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the shotgun sequencing of wastewater can provide information on several viruses simultaneously [ 32 , 33 , 34 ] and enables resolved genomic [ 35 ] and phylogenetic analyses [ 36 , 37 ]. Only a few recent studies have identified known genotypes of SARS-CoV-2, in addition to as-yet-unobserved variants from RNA recovered from the sewers [ 38 , 39 , 40 , 41 , 42 , 43 ], but these studies remain very marginal. Performing the detection of the variants using genome sequencing in multiple sewage water samples is also probably unaffordable in many regions, which are poorly equipped with a sequencing capacity.…”
Section: Introductionmentioning
confidence: 99%